HtrA1 activation is driven by an allosteric mechanism of inter-monomer communication. Issue 1 (December 2017) - Cabrera, Alvaro; Melo, Esther; Roth, Doris; Topp, Andreas; Delobel, Frederic; Stucki, Corinne; Chen, Chia-yi; Jakob, Peter; Banfai, Balazs; Dunkley, Tom; Schilling, Oliver; Huber, Sylwia; et al.
Abstract The human protease family HtrA is responsible for preventing protein misfolding and mislocalization, and a key player in several cellular processes. Among these, HtrA1 is implicated in several cancers, cerebrovascular disease and age-related macular degeneration. Currently, HtrA1 activation is not fully characterized and relevant for drug-targeting this protease. Our work provides a mechanistic step-by-step description of HtrA1 activation and regulation. We report that the HtrA1 trimer is regulated by an allosteric mechanism by which monomers relay the activation signal to each other, in a PDZ-domain independent fashion. Notably, we show that inhibitor binding is precluded if HtrA1 monomers cannot communicate with each other. Our study establishes how HtrA1 trimerization plays a fundamental role in proteolytic activity. Moreover, it offers a structural explanation for HtrA1-defective pathologies as well as mechanistic insights into the degradation of complex extracellular fibrils such as tubulin, amyloid beta and tau that belong to the repertoire of HtrA1.